1977
DOI: 10.1029/gl004i005p00183
|View full text |Cite
|
Sign up to set email alerts
|

High pressure NaAlSiO4: The first silicate calcium ferrite isotype

Abstract: Nepheline (NaAlSiO4)has been transformed at about 1000° C and pressures greater than 180 kbar to a new phase possessing the calcium ferrite structure in a diamond‐anvil press employing YAG laser heating. The unit‐cell dimensions of the high‐pressure phase at STP are ao = 8.740 ± 0.007, bo = 2.746 ± 0.002, Co = 10.206 ± 0.008 Å for indexing as space group Pnma with Z=4. The zero‐pressure volume change associated with nepheline → calcium ferrite structure is −31.9%, and that with Jadeite + α‐NaAlO2 (the intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 9 publications
0
27
0
2
Order By: Relevance
“…There need not be a discrepancy between these findings, however, as Kesson et al relied entirely on TEM, which probes only a small fraction of the sample. It is also possible that the incorporation of Si and Na into the A1-rich phase [Irifune and Ringwood, 1993;Kesson et al, 1994] may enhance the stability of the CaFe20 n structure because NaAISiO n adopts this structure above 18 GPa [Liu, 1977]. By combining TEM (necessarily on quenched samples) with X ray diffraction both at high pressures (and ideally high temperatures) and after quenching to ambient conditions, it should be possible to clarify the phase relations for MORB throughout the pressure range of the lower mantle.…”
Section: Petrologyinmentioning
confidence: 99%
“…There need not be a discrepancy between these findings, however, as Kesson et al relied entirely on TEM, which probes only a small fraction of the sample. It is also possible that the incorporation of Si and Na into the A1-rich phase [Irifune and Ringwood, 1993;Kesson et al, 1994] may enhance the stability of the CaFe20 n structure because NaAISiO n adopts this structure above 18 GPa [Liu, 1977]. By combining TEM (necessarily on quenched samples) with X ray diffraction both at high pressures (and ideally high temperatures) and after quenching to ambient conditions, it should be possible to clarify the phase relations for MORB throughout the pressure range of the lower mantle.…”
Section: Petrologyinmentioning
confidence: 99%
“…High-pressure studies of NaAIGeO4 (Ringwood & Major, 1967a; and NaA1SiO4 (Liu, 1977c(Liu, , 1978aYamada, Matsui & Ito, 1983) revealed that these compounds adopt the orthorhombic calcium ferrite (CaFe204) structure in which all Si and AI are in octahedral coordination. Yamada et al (1983), who synthesized NaAISiO4 at pressures above 24 GPa, used X-ray diffraction to identify their polycrystalline product and propose atomic coordinates.…”
Section: High-pressure Silicates With All Rv~]simentioning
confidence: 99%
“…Moreover, high-pressure induced phase transformations of several electrode materials, e.g., Li x MPO 4 (M ¼ Fe and Co), 8,9 16 In addition to these high-pressure polymorphs of current electrode materials, many novel alkali compounds with an open-channel structure have been derived at high pressure. 12,[17][18][19] It has been proven that these channels likely provide a diffusion path for the alkali ions and lead to high ionic conductivities. 12,18 Although these materials have potential application for batteries, related investigations are rare.…”
Section: Introductionmentioning
confidence: 99%